Association between admission-blood-glucose-to-albumin ratio and clinical outcomes in patients with ST-elevation myocardial infarction undergoing percutaneous coronary intervention - Zhen, Cien; Chen, Wei; Chen, Weikun; Fan, Hualin; Lin, Zijing; Zeng, Lihuan; Lin, Zehuo; He, Weibin; Li, Yu; Peng, Shimin; Zeng, Lin; Duan, Chongyang; et al. (Frontiers in Cardiovascular Medicine, 2023)
It is unclear whether admission blood glucose to albumin ratio (AAR) predicts clinical adverse outcomes in patients with ST-segment elevation myocardial infarction (STEMI) treated with percutaneous coronary intervention (PCI). Here, we performed the retrospective study to explore the 2 This is a provisional file, not the final typeset article predictive value of AAR. Patients diagnosed with STEMI undergoing PCI between January 2010 and February 2020 were enrolled. The patients were classified into three groups according to AAR tertiles. In-hospital all-cause mortality was regarded as the primary outcome and the secondary outcomes were in-hospital major adverse cardiac events (MACEs), as well as all-cause mortality and MACEs during following up. Logistic regression, Kaplan-Meier analysis and Cox proportional hazard regression were mainly used to estimate outcomes. Among the 3,224 enrolled patients, 130 (3.9%) of them suffered in-hospital all-cause mortality and 181 (5.4%) experienced major adverse cardiac events (MACEs). After the adjustment, multivariate analysis demonstrated that an increase in AAR was associated with the increased risk of in-hospital all-cause mortality (adjusted OR: 2.72, 95% CI: 1.47 -5.03, P = 0.001) and MACEs (adjusted OR: 1.91, 95% CI: 1.18 -3.10, P = 0.009), as well as for long-term all-cause mortality (adjusted HR: 1.64, 95% CI: 1.19 -2.28, P = 0.003) and MACEs (adjusted HR: 1.58, 95% CI: 1.16 -2.14, P = 0.003). ROC analysis indicated that AAR could accurately predict in-hospital all-cause mortality (AUC = 0.718, 95% CI: 0.675-0.761) and MACEs (AUC = 0.672, 95% CI: 0.631-0.712). AAR is a novel and convenient independent predictor of all-cause mortality and MACEs both at the in-hospital and long-term levels in STEMI patients receiving PCI.